2016
DOI: 10.1353/hpu.2016.0054
|View full text |Cite
|
Sign up to set email alerts
|

History of Sex Exchange in Women with a History of Incarceration

Abstract: Sex exchange among incarcerated women is not well-described in the literature. Sex exchange can lead to numerous adverse health outcomes, especially when combined with individual factors (e.g., depression and homelessness) and larger systemic inequalities. The purpose of this study was to explore factors associated with having a history of sex exchange among a sample of incarcerated women. Of 257 women surveyed in this study, 68 women (26.5%) reported a history of sex exchange. In multivariate logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
2
8
0
1
Order By: Relevance
“…A qualitative study regarding jail-based contraception among incarcerated women on Rikers Island found that participants supported such services because incarceration was the only point of access for needed medical care, findings that echo the circumstances of the trafficked population in our study [17]. Furthermore, quantitative studies of the risk factors and health issues associated with incarcerated women with histories of sex exchange (of which trafficking survivors are a potential subset) suggest that identifying this history at the time of incarceration can be critical in coordinating appropriate care and post-release services for these populations [18,19].…”
Section: Discussionsupporting
confidence: 63%
“…A qualitative study regarding jail-based contraception among incarcerated women on Rikers Island found that participants supported such services because incarceration was the only point of access for needed medical care, findings that echo the circumstances of the trafficked population in our study [17]. Furthermore, quantitative studies of the risk factors and health issues associated with incarcerated women with histories of sex exchange (of which trafficking survivors are a potential subset) suggest that identifying this history at the time of incarceration can be critical in coordinating appropriate care and post-release services for these populations [18,19].…”
Section: Discussionsupporting
confidence: 63%
“…8 In addition, there is considerable overlap between histories of sex work, substance use, and incarceration among women. 11 Given these risk factors, improved approaches to HIV prevention are needed among individuals who engage in sex work.…”
Section: Introductionmentioning
confidence: 99%
“…Women with criminal-justice involvement are among the most vulnerable and heavily impacted by HIV [1], consistently reporting high rates of both sex and drug risk behavior [2, 3, 62, 63]. The link between risk behavior and incarceration is unsurprising given that many of the behaviors that place women at risk for HIV, such as injection drug use and transactional sex, also put them at risk for incarceration.…”
Section: Discussionmentioning
confidence: 99%